Analysis of Biosorption of Zn (II) ions onto Chemically Modified Saw Dust By using Various Parameters - Shrestha, Bindra; Rijal, Sangita; Poudel, Sumita; Dawadi, Sonika; Humagain, Surendra (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
This study explored biosorption study of Zn (II) onto raw saw dust (RSD) and modified saw dust (MSD) prepared by using saw dust. The adsorption capacity was determined at equilibrium with the help of batch adsorption technique using different parameters like pH of solution, contact time of adsorbent, initial concentration of metal ions and biosorbent dose. Spectrophotometric analysis of resultant sample shows that the loading capacity of adsorbent increases as the pH value increases attaining maximum adsorption at pH 6. The zinc adsorption on both raw and modified adsorbent was found to follow pseudo second order kinetics. The contact time at equilibrium for the adsorption was found to be at 60 and 120 mins respectively. Maximum percentage removal of Zn (II) was found to be 54.23% for RSD which increases up to 66.6 % for MSD maximum at 0.15g of adsorbent in 20 ml metal solution. The results indicate that the chemically modified saw dust can be a low cost alternative to commercial adsorbents for the Zn (II) removal from its aqueous solution.